2021
DOI: 10.1021/acsbiomaterials.1c00980
|View full text |Cite
|
Sign up to set email alerts
|

Facile Fabrication of Hollow Hydrogel Microfiber via 3D Printing-Assisted Microfluidics and Its Application as a Biomimetic Blood Capillary

Abstract: Simulating the structure and function of blood capillaries is very important for an in-depth insight into their role in the human body and treatment of capillary-related diseases. Due to the similar composition and structure, hollow hydrogel microfibers are well-recognized as potential biomimetic blood capillaries. In this paper, we report a novel, facile, and reproducible method to fabricate coaxial microfluidic chips via 3D printing-assisted soft lithography and then hollow hydrogel microfibers using the as-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…Extrusion 3D printing is an emerging microfiber fabrication technology, which can precisely control the size of microfibers and form hierarchical structures by stacking them layer by layer. 23,36,37 This strategy is usually applied to build macroscopic architecture with microfibers. However, the shape of the pulp cavity is irregular, and it is difficult for the preformed scaffold material to fill the entire cavity.…”
Section: Discussionmentioning
confidence: 99%
“…Extrusion 3D printing is an emerging microfiber fabrication technology, which can precisely control the size of microfibers and form hierarchical structures by stacking them layer by layer. 23,36,37 This strategy is usually applied to build macroscopic architecture with microfibers. However, the shape of the pulp cavity is irregular, and it is difficult for the preformed scaffold material to fill the entire cavity.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the supernatants of the corresponding samples were colorless and transparent, with many red blood cells deposited on the bottom of the EP tube, indicating that the nanoparticles did not destroy the red blood cells. When the concentration was up to 3.492 µg/mL, which is much higher than MIC, the hemolysis rate was about 4%, which still did not exceed the national standard (5%) [45]. Therefore, it could be concluded that Ce6-TPP-PEI exhibited negligible obvious hemolysis, meeting the requirements of the hemolysis experiment of biomedical materials.…”
Section: Hemolysis Assaymentioning
confidence: 79%
“…The result suggests that neither the hydrogel scaffold itself nor the burst release of VEGF from the scaffold can induce the formation of substantial blood vessels, further proving the important role of sustained-release VEGF on angiogenesis. CD31, a characteristic protein expressed on the surface of vascular endothelial cells, is often used to indicate the new-born blood vessels [ 55 , 56 ]. The CD31 staining results in Fig.…”
Section: Resultsmentioning
confidence: 99%